2002
DOI: 10.1097/00001888-200202000-00005
|View full text |Cite
|
Sign up to set email alerts
|

How Do Medical Schools Use Measurement Systems to Track Faculty Activity and Productivity in Teaching?

Abstract: The authors describe their findings from a study that (1) identified 41 medical schools or medical school departments that used metric systems to quantify faculty activity and productivity in teaching and (2) analyzed the purposes and progress of those systems. Among the reasons articulated for developing these systems, the most common was to identify a "rational" method for distributing funds to departments. More generally, institutions wanted to emphasize the importance of the school's educational mission. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(19 citation statements)
references
References 13 publications
0
16
0
3
Order By: Relevance
“…A review in 2002 identified 41 schools that were using some kind of metric to quantify teaching activity [18]. Structured interviews with the schools' leadership identified a number of different and sometimes conflicting objectives for these projects: (1) to develop a systematic way to distribute funding, (2) to track the resources spent on teaching for the purpose of required reporting, (3) to address chairs' mistrust of the dean's office, (4) to counter the "myth" that faculty cannot afford to teach or are not compensated, (5) to provide incentives to teach, and (6) to raise the visibility and thus the value of teaching.…”
Section: Some Possible Solutionsmentioning
confidence: 99%
“…A review in 2002 identified 41 schools that were using some kind of metric to quantify teaching activity [18]. Structured interviews with the schools' leadership identified a number of different and sometimes conflicting objectives for these projects: (1) to develop a systematic way to distribute funding, (2) to track the resources spent on teaching for the purpose of required reporting, (3) to address chairs' mistrust of the dean's office, (4) to counter the "myth" that faculty cannot afford to teach or are not compensated, (5) to provide incentives to teach, and (6) to raise the visibility and thus the value of teaching.…”
Section: Some Possible Solutionsmentioning
confidence: 99%
“…Pololi et al, 5 for instance, have already described faculty's desire that institutions "assign appropriate value to non-income-producing activities." Clinical faculty's educational efforts are measured in relative value units (RVUs), which are evaluated in two key ways 6 : the contact hour method (estimating the time allocated to educational efforts) and the relative value method (estimating the educational efforts, analogous to the resource-based relative value scale for clinical activities). Educational RVU systems have been developed by local departments and specific persons 7-12 and by organizations and medical councils, 13,14 the latter exemplified by the visionary and important report by Nutter and colleagues 14 for the Association of American Medical Colleges (AAMC).…”
Section: Inabusyclinicalsettingwherethehealthmentioning
confidence: 99%
“…Reconnaître l'enseignement comme une authentique activité universitaire, notamment pour des décisions de recrutement ou de promotion, implique d'évaluer cette activité. Différentes approches de ce type d'évaluation sont rapportées dans la littérature [8][9][10][11][12][13][14][15][16] . La majorité des expériences publiées concerne des systè-mes de quantification des activités d'éducation.…”
Section: Résultatsunclassified